Superattracting Cycles for Some Newton Type Iterative Methods - Plaza, S (SCIENCE CHINA PRESS, 2011)
The paper is devoted to the analysis of certain dynamical properties of a family of iterative Newton type methods used to find roots of non-linear equations. We present a procedure for constructing polynomials in such a way that superattracting cycles of any prescribed length occur when these iterative methods are applied. This paper completes the study begun in Amat, Bermúclez, Busquier, et al., (2009). © 2011 Science China Press and Springer-Verlag Berlin Heidelberg.